Green Village Pertamina Integrated Terminal Surabaya: Strategy of Corporate Social Responsibility (CSR) Towards the Sustainable development Goals (SDGs) - Aulia Ulfah Farahdiba; Anis Yuzrin Qonita; Eddy Kurniawan (Nusantara Science and Technology Proceedings)
This study developed Corporate Social Responsible (CSR) to enhance the Sustainable Development Goals (SDGs) with the Pertamina Integrated Terminal Surabaya program. The company needs to strengthen its engagement with nearby villagers, and alignment between CSR efforts and community needs. Influenced Suitable program must have been considering based on condition, community potential, and capability from each district. District Perak Utara and District Jagir Surabaya have become the green village at Surabaya. Data collection within the previous conditions and the program developed has been analyzed. Research recommends active engagement within the community in decision making at all stages of community development in each program that gives exclusive powers to traditional leaders or cadre.